2014
DOI: 10.1111/1471-0528.13163
|View full text |Cite
|
Sign up to set email alerts
|

Hot flushes and night sweats are associated with coronary heart disease risk in midlife: a longitudinal study

Abstract: Objective The purpose of this study was to investigate associations between vasomotor menopausal symptoms (VMS), i.e. hot flushes and night sweats, and the incidence of coronary heart disease (CHD).Design A prospective cohort study.Setting and population 11 725 women, aged 45-50 years at baseline in 1996, were followed up at 3-year intervals for 14 years.Methods Self-reported VMS and incident CHD were measured at each survey.Main outcome measure We determined the association between VMS and CHD at the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 31 publications
1
24
0
5
Order By: Relevance
“…Women with severe hot flushes may have an increased sympathetic tone with vascular involvement 15 . What is, however, now clear is that hot flushes (previously thought to be solely due to decreased estrogen levels) are a complex multicausal phenomenon and reflect a combination of interconnected systems including genetic bases, diet, physical changes, use of medications, cultural influences, and individual experiences and expectations [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Women with severe hot flushes may have an increased sympathetic tone with vascular involvement 15 . What is, however, now clear is that hot flushes (previously thought to be solely due to decreased estrogen levels) are a complex multicausal phenomenon and reflect a combination of interconnected systems including genetic bases, diet, physical changes, use of medications, cultural influences, and individual experiences and expectations [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Although findings are not entirely consistent, with one study finding VMS to be associated with a decreased risk of cardiovascular disease mortality 3 , several recent studies suggest that VMS frequency and/or severity may be positively associated with cardiovascular disease risk. In one 14-year longitudinal study of over 11,000 women aged 45-50, women who reported having VMS ‘often’ had a two-fold increased risk of developing coronary heart disease (CHD) over the course of the study when compared to women who reported no VMS 4 . Furthermore, the Women's Health Initiative Observational Study (WHIOS), involving approximately 60,000 postmenopausal women aged 50 to 79 who were followed for an average of 9.7 years, 5 found that VMS, particularly late-onset VMS, were associated with an increased risk of major CHD, stroke and total cardiovascular disease (HRs = 1.30-1.46).…”
mentioning
confidence: 99%
“…High vasomotor symptoms are associated with overactive of the sympathetic nervous system, and sympathetic overdrive in turn is associated with metabolic symptoms, which is a known risk factor of CVDs (Tuomiloski, & Savolainen-Peltonen, 2017). In addition, in a longitudinal study, it was confirmed that women having hot flushes or night sweats often had an increased risk of developing coronary heart diseases (Herber-Gast, Brown, & Mishar, 2015). Furthermore, it is known that women with CVDs report atypical symptoms such as unusal fatigue, sleep disturbance, nausea, vomiting, dyspena, and weakness rather than typical cardiovascular symptoms (McSweeney et al, 2010).…”
Section: Discussionmentioning
confidence: 94%